PHYTOCHEMICAL PROFILE AND ANTIBACTERIAL POTENTIAL OF METHANOL EXTRACTS OF Artocarpus kemando MIQ. BRANCH BARK AGAINST Bacillus subtilis - Andini, Vicka; Dwiwibangga, Yoravika; Arman, Etriyanto; Elfia, Mega (Tanjungpura University, 2025)
Artocarpus kemando Miq., a member of the Moraceae family, is found in tropical regions of Indonesia, including Karang Anyar, South Lampung. This study aimed to qualitatively analyze the phytochemical content and evaluate the antibacterial activity of the methanol extract of Pudau branch bark against Bacillus subtilis. The extraction was performed using the maceration method with methanol as the solvent. Phytochemical screening was conducted in triplicate and revealed the presence of alkaloids, flavonoids, terpenoids, and saponins, while steroids were absent. Antibacterial activity was assessed in triplicate using the paper disc diffusion method, with results showing moderate activity of the extract, indicated by an average inhibition zone diameter of 10.33 mm. Statistical analysis using one-way ANOVA revealed a significant difference in the average inhibition zone diameters among the treatment groups (methanol extract, negative control, and positive control) with a p-value of 0.000. Tukey HSD post hoc analysis confirmed that the methanol extract exhibited significantly higher antibacterial activity than the negative control, but significantly lower than the standard antibiotic amoxicillin (22.67 mm). These results highlight the potential of A. kemando Miq. Branch bark extract is a natural antibacterial agent, although its efficacy remains lower than the standard antibiotic (amoxicillin).